2007
DOI: 10.1111/j.1747-0765.2007.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of the contribution of the phloem in cadmium transport to grains in rice plants (Oryza sativaL.)

Abstract: The contribution of the phloem in translocation of cadmium (Cd) to grains of rice plants (Oryza sativa L. cv. Kantou) was estimated. We measured Cd concentrations in phloem sap collected from the uppermost internode of rice plants at the grain-filling stage. Cadmium concentration was 17.8 ± 4.5 µmol L −1 in plants treated with a nutrient solution containing 10 µmol L −1 Cd for 2 days. Subsequently, distribution ratios of 109Cd between the grains and the glumes were determined after feeding of 109Cd to the cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 13 publications
2
85
0
1
Order By: Relevance
“…This explains why husk concentrations of As in the first experiment were also markedly higher for the DMA treatment than those for inorganic arsenite. It has been suggested that as a nontranspiring tissue developing grain will be fed assimilates primarily via phloem transport, and the actively transpiring husk primarily via the xylem (Tanaka et al, 2007;). This appears evident in the high concentrations of the phloem marker, Rb, compared with the comparatively low grain levels Sr.…”
Section: Discussion As Speciation and Accumulation In Grainmentioning
confidence: 99%
“…This explains why husk concentrations of As in the first experiment were also markedly higher for the DMA treatment than those for inorganic arsenite. It has been suggested that as a nontranspiring tissue developing grain will be fed assimilates primarily via phloem transport, and the actively transpiring husk primarily via the xylem (Tanaka et al, 2007;). This appears evident in the high concentrations of the phloem marker, Rb, compared with the comparatively low grain levels Sr.…”
Section: Discussion As Speciation and Accumulation In Grainmentioning
confidence: 99%
“…Phloem transport has also been considered a key step of Cd translocation to the grain, because xylem transport is directed mainly to the organs of highest transpiration, such as leaves, but not to the sites of highest demand for mineral, such as grains (Marschner, 1995). Cd was detected in the phloem sap of rice collected from leaf sheaths (Tanaka et al, 2003) and from the uppermost internode at the grain-filling stage (Tanaka et al, 2007). Tanaka et al (2007) also estimated that 91% to 100% of Cd in rice grains is deposited from the phloem.…”
mentioning
confidence: 99%
“…Cd was detected in the phloem sap of rice collected from leaf sheaths (Tanaka et al, 2003) and from the uppermost internode at the grain-filling stage (Tanaka et al, 2007). Tanaka et al (2007) also estimated that 91% to 100% of Cd in rice grains is deposited from the phloem. In wheat, it has been observed in a split-root system that Cd fed to one bundle of the roots moved into the other bundle, probably via the phloem (Welch et al, 1999;Page and Feller, 2005), and steam girdling, which stops only phloem transport but not xylem flow, to the peduncle below the ear reduced Cd translocation to the grain (Riesen and Feller, 2005).…”
mentioning
confidence: 99%
“…Phloem-mediated Cd transport to grains following xylem-mediated root-to-shoot translocation is critical for the accumulation of Cd in rice grains. Nearly 100% of the Cd in rice grains is attributable to phloem transport (22,23). Fujimaki et al (22) used a noninvasive live imaging technique to follow the transport of 107 Cd in intact rice plants.…”
mentioning
confidence: 99%